PENGARUH IKLIM ORGANISASI DAN KOMUNIKASI DIGITAL TERHADAP KINERJA KARYAWAN DENGAN INOVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Perhotelan Kawasan Bandungan) - Fania Lailatul Kamalia; Edy Raharja (Faculty of Economics and Business Diponegoro University, 2022)
The purpose of this study was to determine the effect of Organizational Climate, Digital Communication, and Work Innovation on Employee Performance. Based on the data, there has been a successive decline in performance in the last three years, namely 2017-2019 at the hotel that is the object of research. With the phenomenon of the decline in performance, the authors used as the basis for conducting this research. On the other hand, it was found that there were contradictory results from previous research on the influence of organizational climate and digital communication on employee performance which proved to have a significant and insignificant effect. This shows that efforts to improve employee performance through organizational climate factors and digital communication still cannot ensure a harmonious relationship. The data used in this study is primary data in the form of questionnaires as many as 50 respondents of hotel employees in the Bandungan area who are hotel employees of Amanda Hills, Kusma Madya, and Tri Buana. The sampling technique used in this research is random sampling. The analysis of this research uses Partial Least Square (PLS). This research data processing using SmartPLS software version 3.2.8. The results showed that (1) Organizational climate had a positive and significant effect on employee performance. (2) Organizational climate has a positive and significant effect on Job Innovation. (3) Digital Communication has a positive and significant effect on Employee Performance. (4) Digital Communication has a positive and significant effect on Work Innovation. (5) Work Innovation has a positive and significant effect on Employee Performance.